Community Empowerment towards Healthy Living through The Implementation of Healthy Living Community Movements (GERMAS): GERMAS - Siregar, Fazidah A (Talenta Publisher Universitas Sumatera Utara, 2020)
Indonesia is currently facing a triple burden of disease where the incidence of non-communicable diseases is increasing. The condition is related to lifestyle include lack of physical activity, an unhealthy and unbalanced diet, and unhealthy lifestyle as smoking and alcohol consumption. To educate the community to implement healthy living, GERMAS is being promoted, emphasizing promotive and preventive efforts. The purpose of these activities was to educate and mobilize the community to implement healthy living by implementing GERMAS that focuses on physical activities, consuming vegetables and fruit, and checking health regularly. From the health status monitoring, 15.6% of participants were in the systolic prehypertension stage, and 34.4% were in the systolic hypertension stage, 19.0% with high cholesterol levels, 43.8% with high uric acid levels and 21.9% with high blood sugar levels. This activity was continued by giving education about balanced and healthy food, routine physical activities during three months and the use of their yards for planting vegetables and fruit and motivating the communities for consuming the healthy food daily. After three months,Â the health condition improved in which the number of participants with systolic hypertension and high blood sugar levels decreased to 30% and 12.5%, respectively. It was concluded that the implementation of healthy life society movement daily could reduce the biological risk factors leading to the reduction of non-communicable disease incidence.